KEBERSIHAN DALAM KONSEPSI ISLAM DAN KRISTEN - Kamaluddin Kamaluddin; Uqbatul Khoir Rambe; Rizky Annisa Fitri (Studia Sosia Religia, 2021)
Cleanliness is very important for every human being. Cleanliness is one of the main efforts in maintaining human existence. Religion gives very high attention to cleanliness, both physically and mentally. This research is a literature research "library research" which is a research conducted systematically by collecting data from several books or other sources of scientific work related to the title. The sources used are mandatory primary sources and secondary sources that are used to support the author. This research is a comparative study that attempts to compare the two existing theories, in order to gain understanding and the concept of cleanliness from Islam and Christianity and to be able to conclude the similarities and differences of the concept of cleanliness of the two religions. The focus of the research is to describe the concept of cleanliness that is believed by both religions namely Islam with taharah and Christianity with baptism. The concept of cleanliness in Islam is taharah while in Christianity it is baptism. The concept of taharah is a complete explanation of anything related to cleanliness, whether it is clean outwardly (body, place, environment) or spiritually (belief and soul). The concept of baptism in Christianity is more about physical and spiritual cleanliness which is related to clean morals and behavior. The purpose of this study is to know the meaning of cleanliness in general and specifically and to know the importance of maintaining cleanliness in the concept of Islam and Christianity.